Soil bacterial diversity in the Zaamar mining area, Mongolia - Narantuya, Damdinsuren; Battsetseg, Choidash; Naranjargal, Sodbaatar (Proceedings of the Institute of Biology, 2022)
The bacterial diversity of the sample BM from the non-interacted mining area was significantly abundant compared to mining interacted samples. Nine phyla were dominant in the bacterial community structure. But in samples from the mining operation area sample VBKB-b and abandoned mining sample are VBKB-b, 3 phyla Firmicutes (59-66%), Actinobacteria (17.4-26.8%), Proteobacteria (11-14%) were dominant in the bacterial community.